2005
DOI: 10.1111/j.1365-4632.2004.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin disease: clinical indicator of immune status in human immunodeficiency virus (HIV) infection

Abstract: There was an inverse relation between the CD(4) counts and the incidence and severity of skin diseases in the HIV/AIDS patients. Cutaneous manifestations of HIV can be considered as good clinical indicators to predict and access the underlying immune status in resource-poor countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 18 publications
10
39
3
2
Order By: Relevance
“…(6)(7)(8)(9) It may be the presenting feature and a valuable clinical tool in staging and predicting progression of the disease. (10)(11)(12)(13)(14)(15) …”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9) It may be the presenting feature and a valuable clinical tool in staging and predicting progression of the disease. (10)(11)(12)(13)(14)(15) …”
Section: Introductionmentioning
confidence: 99%
“…In our study Molluscum contagiosum was reported as 5.19% which coincides with the findings of Kore et al 20 Among non-infectious manifestations, Xerosis was the most common and reported with prevalence of 31.37%, these findings were on contrary with findings of Raju who reported the prevalence as 22.17% in his study, but similar to Kumaraswamy et al who reported as 37% in his study. 21,22 Followed in next order, generalized pigmentation was observed with 19.61% prevalence and Seborrhoeic dermatitis in 23.53%. The prevalence of pigmentation and seborrhoeic dermatitis was considerably less than in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that dermatological manifestations are seen at every stage of HIV/ AIDS and are often the presenting feature 1 . These manifestations not only act as disease markers, but also reflect the underlying immune status 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which HIV-infected patients are prone to skin disease appears to be correlated with the degree of immunodeficiency 4 . Many skin diseases may in fact be considered valuable and sensitive indicators for the diagnosis of HIV and for monitoring disease progression and treatment efficacy 5,6 . The hallmark of HIV infection is a progressive, qualitative and quantitative deficiency of helper CD4 T lymphocyte which is needed for foreign antigen presentation and phagocytosis.…”
Section: Introductionmentioning
confidence: 99%